Pengaruh Intellectual Capital terhadap Kinerja Usaha Mikro yang Dimediasi oleh Perilaku Kerja Inovatif - Ida Subaida; Rini Kartikasari (Fakultas Ekonomi Universitas Kadiri, 2020)
Economic globalization is characterized by the implementation of technology and knowledge, companies are faced with the challenges of technological change and improvement in the global business environment. Knowledge and technology can be reflected in intellectual capital. Intellectual capital represents knowledge in an organization at a particular time. Intellectual capital owned by the company will lead to innovative work behavior. Intellectual capital has also received attention from both the academic community and companies because of the influence of innovation and learning on achieving competitive advantage for companies in new or knowledge-based economies. The purpose of this research is that this study wants to examine both the direct effect of intellectual capital on company performance and the indirect effect through innovative work behavior. This research was conducted on micro businesses in Situbondo District, Situbondo Regency. Data analysis methods in this research were descriptive statistics and testing the outer and inner models using PLS Warp. The results show that intellectual capital directly does not affect innovative work behavior, intellectual capital directly influences the performance of micro businesses, and intellectual capital indirectly through innovative work behavior does not affect the performance of micro businesses.